The inclusiveness of culture economy in promoting the growth of East Coast Economic Region. case study : Kelantan Malaysia / Assoc. Prof. Dr. Fatimah Yusof … [et al.] - Assoc. Prof. Dr. Fatimah Yusof (Research Management Institute (RMI), 2013)
The production of culture in economic and urban landscape has received much attention within geography realm. The contribution of culture such as art, food, craft, design, textile and fashion can be preserved as a source of inspiration to produce new innovative products, added value and competitive advantage of a region. On the other hand, cultural economic geography is also about how people and their culture interact with their environments, how goods, services and ideas move across space, enriching reputation and skills of the local. Thus, this paper intends to provide framework for a global understanding of cultural economic geography in the East Corridor Economic Region, particularly in Kelantan State, Malaysia. It will discuss the structure and discourses embedded in the ECER Development Plan in changing the cultural production and of cultural work; and, the 'culturalisation' of the economy. This paper will also review the culture landscape and performance of Kelantan's local communities across times and space, how they create skills, values and landscape for their complete places and lives, yielding place that provides economy. Finally, the paper will explore issues associated with the local cultural innovation; in particular, re-positioning of the cultural economy in relation to its production/consumption, and the economic /sociocultural.